2015
DOI: 10.1177/0020764015577841
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of vocational status in schizophrenia patients – Results from the Polish nationwide survey

Abstract: Background:Steady employment constitutes one of most important aspects of functional recovery in schizophrenia. Therefore, there is a need for understanding clinical and demographic factors predicting vocational status in schizophrenia.Methods:Clinical and demographic data of 1,010 schizophrenia patients were gathered from public outpatient clinics. We compared patients who maintained employment between the diagnosis time point and the day of assessment, with the patients who were employed in the diagnosis tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
3
2
Order By: Relevance
“…This might be due to in the severe stage of the illness behavioral and thought disorganization are prominent which affects functional involvement. This was consistent with studies conducted in Poland [22] and the European schizophrenia cohort study (EURO SC) [28].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…This might be due to in the severe stage of the illness behavioral and thought disorganization are prominent which affects functional involvement. This was consistent with studies conducted in Poland [22] and the European schizophrenia cohort study (EURO SC) [28].…”
Section: Plos Onesupporting
confidence: 92%
“…duration of the study and previous job status of the participants in which ours were only those who had job during first diagnosis. This study was slightly lower than the study done in Poland which was 43.9% [22]. The possible reason might be due to accesses of higher training and job position in developed nations require increased mental functioning that is difficult for schizophrenia patients to maintain their job.…”
Section: Plos Onecontrasting
confidence: 67%
See 1 more Smart Citation
“…The rate of employment in our sample is higher than the rates reported in previous studies in developed countries (11)(12)(13)(14)(15)(16)(17), but lower than the rate reported in an urban area in India (19). In general, Singapore has a low unemployment rate (39,40) and Warner (41) had proposed that employment rate in people with schizophrenia may be associated with the prevailing economic condition and unemployment rate in the general population.…”
Section: Discussioncontrasting
confidence: 64%
“…Illness onset during adolescence and early adulthood (9) interferes with an individual's vocational development such as education and employment (10). Among people with schizophrenia, the reported employment rate ranged from 10.2% in Norway to 30.3% in Germany (11)(12)(13)(14)(15)(16)(17). Employment rate was higher in developing countries, Asia (18,19), and in rural areas (13,18,20).…”
Section: Introductionmentioning
confidence: 99%